ANALISIS PEMERINTAHAN DALAM PROGRAM PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) Studi Kasus di Kecamatan Semarang Barat Kota Semarang - Rahmawati Among; Teguh Yuwono; Dzunuwanus Manar (Journal of Politic and Government Studies, 2017)
The Governance Analyisis on District Integrated Administrative Services (PATEN) Programe: Case Study In West Semarang District of Semarang City aims to explain any innovations that contained in PATEN, how the innovation was done, the underlying reasons of Semarang City Goverment on making decisions about PATEN Programe which only held in non-permission services, and the impact for society as service users in West Semarang District about the implementation of PATEN. The method of research used in this study is Mixed Method Research with concurrent embedded strategy, which both qualitative and quantitative data were collected at the same time. For collecting data, researcher conducted interviews at the office of West Semarang District and the government of Semarang City and then distributed questionnaire to communities in the region of West Semarang District. Researcher also used secondary data from documents of PATEN and other literature sources such as books and journals. The implementation of PATEN brings about changes in performance of employee districts and has impact for the community. The presence of PATEN is not only to improve the quality of service in the district but also for a better and closer service to the community. The changes that occur through of PATEN such as more modern service system, establishment of service standards, and the provision of service facilities. In implementation of PATEN, the government of Semarang City has several considerations include the substantive requirements have not been met, sectoral ego among departments, barriers on standard of implementation, outside of the priority scale, the new constitution of local government, conditions of urban area, and the indecisiveness of sanctions of the central government. Furthermore, as the impact for the community, PATEN was able to provide a positive impact although most people said that they did not know about PATEN in Semarang City. Therefore, the government should also involve the community participation, so that in the future the authorities that are delegated to the districts will be suitable to the needs of society. On the other hand, society should be more active in participating to oversee the implementation of public services in the district level.